Bohmian tunneling times in strong-field ionization - Grozdanov, Tasko P.; Solov’ev, Evgeni A. (The European physical journal. D, Atomic, molecular, and optical physics, 2023)
Phenomenon of tunneling ionization became the subject of many theoretical studies inspired by recent attoclock experiments on strong-field ionization of atoms by few-cycle laser pulses in infrared wavelength region. In particular, the notion of electron tunneling time caused a lot of controversy in various theoretical approaches. Bohmian mechanics seems to be specially suitable for theoretical description of electron tunneling times. We present results of calculations of probability distributions of electron Bohmian tunneling times for the model problem of ionization of 1D atom by a half-cycle laser pulse. Two regimes are studied in details: (a) the case of completely tunneling ionization and (b) the case involving three mechanisms: direct, non-completely and completely tunneling ionization. Probability distributions of tunneling exit positions and exit velocities are also studied. In addition, we discuss the appearance of transient dynamical tunneling due to non-adiabatic switching of external field. Graphic Abstract